2020
DOI: 10.1557/mrs.2020.272
|View full text |Cite
|
Sign up to set email alerts
|

Changes in short- and medium-range order in metallic liquids during undercooling

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 84 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…This mechanism has been identified as ISRO-mediated nucleation ( [36], [38], [42], [54]) contributing to grain refinement in the FEZ and also explaining the unexpectedly high density of Σ3 twin boundaries found in the FEZ. ISRO-mediated nucleation occurs when the undercooling is high enough to promote a large proportion of ISRO into the liquid [58]. We think that ISRO-mediated nucleation requires larger undercooling in comparison to the nucleation mechanisms involving primary phases.…”
Section: Grain Refinement Mechanismsmentioning
confidence: 92%
See 1 more Smart Citation
“…This mechanism has been identified as ISRO-mediated nucleation ( [36], [38], [42], [54]) contributing to grain refinement in the FEZ and also explaining the unexpectedly high density of Σ3 twin boundaries found in the FEZ. ISRO-mediated nucleation occurs when the undercooling is high enough to promote a large proportion of ISRO into the liquid [58]. We think that ISRO-mediated nucleation requires larger undercooling in comparison to the nucleation mechanisms involving primary phases.…”
Section: Grain Refinement Mechanismsmentioning
confidence: 92%
“…An EBSD map of the alloy without Zr is shown in Figure 12. No twin dendrites were observed in the alloy version without Zr, a solute known to promote local ordering with coordination numbers larger than 12 in liquid Al, as is indicated by ab initio molecular dynamics calculations [58], [61]. In addition to the problem of twin dendrites nucleation, we also wish to comment on the growth competition between classical columnar grains and feathery grains in the NCZ, see Figure 2.…”
Section: On the Origin Of Twin Dendritesmentioning
confidence: 95%
“…Grain refinement mechanism of undercooled solidification microstructure of binary alloys is a topic of debate for decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For highly undercooled single phase binary alloys, recent studies on Fe-Ni [3], Ni-Cu [4], Fe-Co [6] and Ni-C [9] alloys show that two grain refinement could be found.…”
Section: Introductionmentioning
confidence: 99%
“…Under the condition of deep undercooling, single-phase alloys generally solidify in the form of dendrites. When the initial undercooling degree of the alloy melt is greater than a certain critical value, the solidification structure changes from developed dendrites to fine equiaxed crystals, and the grain size decreases by about 2 orders of magnitude [1][2][3][4][5][6][7][8][9][10] . Kattamis et al found that CuNi alloy presents developed dendrites when undercooling is less than 175 K and fine equiaxed crystals when undercooling is greater than 175 K. Recently, some researchers [4,[11][12][13][14] found that the grain refinement phenomenon of columnar dendrite to equiaxed crystal also exists under small undercooling.…”
Section: Introductionmentioning
confidence: 99%